PENGARUH LATIHAN STRIDE JUMP CROSSOVER TERHADAP POWER OTOT TUNGKAI PADA CLUB BOLA VOLI PUTRA SMVC KECAMATAN TAPUNG - Diky Surya Wahyu; Zainur Zainur; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Based on the results of observations by researchers in the field, the athlete of the Tunas Putra volleyball club, SMVC, Tapung District. Researchers observed that in training sessions and in matches, the athletes of the Men's Volleyball Club, SMVC, Tapung District, still had many shortcomings, one of which was the leg muscles when jumping during smashes and blocks. So that when the smash or block is not optimal, so that the smash is not carried out properly or can be blocked by the opponent, as well as what happened to the SMVC Men's Volleyball Club athlete in the Tapung District at the time of the block, it was so easy for the opponent to smash, as a result in the match always lose. The purpose of this study was to determine the effect of Stride Jump Crossover training on leg muscle power at the SMVC men's volleyball club, Tapung District. The population in this study were 15 men's volleyball club, SMVC, Tapung District. In this study, the sampling technique was carried out by means of total sampling, where the samples were male players who routinely exercised. From the entire population, there are 15 samples. The instrument used in this study was the vertical jump. The data obtained were analyzed using t-test comparisons. Based on data analysis and discussion, it can be concluded that there is an effect of Stride Jump Crossover training on leg muscle power in the men's volleyball club SMVC, Tapung District, proven by the results of tcount 1.790> t table 1.762 at α = 0.05. This proves that by doing the Stride Jump Crossover exercise, the leg muscle power can get better results. Key Words: Stride Jump Crossover Exercise, Leg Muscle Power